JSE's First Retraction - Braude, Stephen (Journal of Scientific Exploration, 2021)
This issue of the JSE includes a retraction of a paper by Alejandro Parra that we published in 2017. As far as I can determine, it’s the journal’s first official retraction of a published paper. The reason for this action is the author’s extensive plagiarism, both in that paper and in other published work (including a recent book whose publisher has since recalled all copies). It’s a sad state of affairs, of course—and perhaps the first of its kind in this particular and admittedly minor scientific domain. But it reminds me that six years ago, in Volume 29(2), we published a paper on retractions in science, and in that issue I seized the opportunity to editorialize further on the subject. I recycle that Editorial below. But before that, I must note that careful examination has found no additional evidence of plagiarism in the one other research article (in 2018) and the one book review we’ve published by Parra. I must also mention that, henceforth, the JSE will run routine plagiarism tests on papers accepted for publication. I thought this was a chore I’d left behind when I retired from teaching. However, I don’t want the JSE to emulate the person who said “I’ve learned from my mistakes, and I’m certain I can repeat them exactly.” EDITORIAL FROM JSE VOLUME 29(2), 189–192